From a long-term dynamic perspective: how should internal carbon pricing be implemented? - Yanfei, Liu; Hejie, Zhu; E, Bai; Long, Li (Frontiers in Energy Research, 2023)
Internal carbon pricing has the potential to positively influence enterprises' carbon emissions. However, the strategies for implementing internal carbon pricing for enterprises and internal organizations remain unclear. In this study, employing a differential game research methodology, we design three implementation strategies for internal carbon pricing from a dynamic time perspective. Through comparative research and numerical analysis of these three different strategies' effects on the changes in enterprise carbon emission reduction and goodwill, we find that for both enterprises' carbon emission reduction and goodwill, Model C (implementing secondary investment for internal carbon fee collection) is optimal when the proportion of internal organizational revenue allocation is high and the proportion coefficient of internal carbon fee collection is low. When the proportion coefficient of internal carbon fee collection meets certain conditions, it makes the total profit of system under model C (implementing secondary investment for internal carbon fee collection) larger than the other two strategies. Due to short-sighted behavior, both enterprises' profits and carbon emissions gradually decrease, leading to the internal carbon prices of enterprises under the three strategies will approach a stable value.